2007
DOI: 10.1590/s0104-56872007000200007
|View full text |Cite
|
Sign up to set email alerts
|

Audiometria de reforço visual com diferentes estímulos sonoros em crianças

Abstract: The MRL decrease with age independently of the stimulus and are lower when using the Sonar System. For the group of children with hearing loss no significant difference was found for any of the studied variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
(19 reference statements)
0
3
0
2
Order By: Relevance
“…The hearing screening was carried out through visual reinforcement audiometry (9) , using a portable pediatric audiometer, with pure modulated tones (warble) in the frequencies of 500, 1,000, 2,000, and 4,000 Hz and intensities from 20 to 80 dBHL. Responses between 20 and 40 dBHL were considered normal (10) .…”
Section: Methodsmentioning
confidence: 99%
“…The hearing screening was carried out through visual reinforcement audiometry (9) , using a portable pediatric audiometer, with pure modulated tones (warble) in the frequencies of 500, 1,000, 2,000, and 4,000 Hz and intensities from 20 to 80 dBHL. Responses between 20 and 40 dBHL were considered normal (10) .…”
Section: Methodsmentioning
confidence: 99%
“…Frequencies were alternated (500, 1000, 2000, 4000 Hz) until reaching the minimum response level for each frequency. Responses between 20 and 40 dB were considered normal (13) . Although this assessment is suitable for children up to two years, it was necessary to extend the age range used, because it was found that children at that age were not able to respond to the playful audiometry.…”
Section: Methodsmentioning
confidence: 99%
“…Com intensidade inicial de 80dBNA, com pesquisa descendente de 10 em 10dB e ascendente de 5 em 5dB, dentro de cabine acústica em campo livre, em cadeira específica ou no colo do responsável em posição medial às caixas de som. Foram consideradas, como reação comportamental frente aos estímulos sonoros, as seguintes respostas: reflexo cocleopalpebral, movimento ocular lateral, localização sonora lateral, aumento ou diminuição da sucção da chupeta, sorriso, choro, atenção, susto, franzir a testa, movimentos generalizados do corpo, entre outros, conforme descrito pela literatura consultada 13,16 . A observação destes comportamentos e as demais testagens foram realizadas por duas fonoaudiólogas avaliadoras e uma estagiária.…”
Section: Quadro 1 -Parâmetros Do Peate-fe Nas Frequências De 500 E 20unclassified
“…A audiometria infantil em campo livre busca identificar respostas comportamentais a estímulos sonoros 15 de tom puro modulado em frequência (warble) apresentados em campo livre, por meio de autofalantes para determinar o nível mínimo de resposta (NMR) 16 . Tal avaliação permite identificar a perda auditiva, quando presente, avaliar o desenvolvimento da função auditiva e a maturação do sistema auditivo central 13 .…”
Section: Introductionunclassified